Reciclagem de PETG para produção de filamentos e aplicação em Manufatura Aditiva - Flores, João Daniel Seno (2021)
In the search for a more sustainable society, one of the main challenges of today is the environmental, social and economic damage caused by the predominance of the linear economy. An alternative is the return of polymeric waste to the production chain (reverse logistics) for application in new manufacturing methods, such as Additive Manufacturing (MA), with an emphasis on Fused Filament Fabrication (FFF). In this aspect, this master's work proposed the application of Poly(ethylene terephthalate) glycol (PETG) residues, arising from the manufacture of Faceshields (Auxiliary EPI to prevent the transmission of Covid-19), for the production of filaments for the FFF. Initially, PETG in flake format was characterized by FTIR, NMR, parallel plate and capillary rheometry, TGA and DSC, identifying in the last it as a semi-crystalline PETG. Subsequently, by simulating 5 cycles of mechanical PETG recycling and obtaining filaments at the end of each cycle, the influence of reprocessing on the rheological and thermal properties of these filaments was evaluated with parallel plate and capillary rheometry tests, TGA and DSC. To analyze the influence of recycling, the 5 filaments were used in the additive fabrication of specimens (Norm ABNT D638 - Type I) with a deposition angle of ± 45° and fabrication quality using a calibration standard (#3DBenchy). Despite the reprocessing causing polymer degradation, verified by the reduction of viscosity and favoring crystallization, all filaments were adequate for application in FFF. In tensile strength there is a growth from the 1st to the 3rd processing cycle and subsequent reduction to the 5th cycle, mainly due to the variation in molar mass and molecular diffusion. In the analysis of manufacturing quality, it was found that the most reprocessed filaments had better surface / dimensional quality due to higher crystallization kinetics.